Is indomethacin harmful in spinal cord injury treatment? An experimental study - Guven, MB; Cirak, B; Yuceer, N; Ozveren, F (Karger, 1999)
This study was designed to analyze the effect of early indomethacin on the lipid peroxidation after spinal cord injury in rats. The use of anti-inflammatory drugs to affect delayed and secondary injury after trauma to the spinal cord has now become a matter of standard clinical practice. However, spinal cord injury remains an enormous clinical problem and research that may lead to improved treatment is to be encouraged and commended. Three experimental groups consisting of 40 rats each were formed. Using microsurgical technique, total laminectomy between T5 and T10 was performed. Spinal cord injury was achieved with an epidural aneurysm clip, and pharmacological treatment immediate after the injury was performed by injecting indomethacin intraperitoneally (i.p.) at a dose of 3 mg/kg to indomethacin-treated group. The three main groups were divided into subgroups of 8 rats each. It was planned to stop the biochemical reactions at a different time in each of these subgroups, by the application of liquid nitrogen to the spinal cord and paravertebral structures at the end of the 1st, 15th, 30th, 60th, and 90th minutes. All the spinal cords were removed and protected from further reactions by immersing in the liquid nitrogen tank. The lipid peroxidation levels were assessed by determining thiobarbituric acid reactive substances formation. The results of the study showed that the administration of 3 mg/kg indomethacin immediately after spinal cord injury induces lipid peroxidation to a significant degree (p < 0.05 one-way ANOVA and Tukey HSD tests) when compared to the saline-treated group. This result suggests that early posttraumatic indomethacin treatment may be harmful in spinal cord injury. Copyright (C) 2000 S. Karger AG, Basel.
Keywords: indomethacin; lipid peroxidation; experimental spinal cord injury; malondialdehyde; free radical